Understanding the structure and interactions of polycystin-2 through structural and simulation studies - Wang, Q (2019)
Polycystin-2 (PC2) is a member of the transient receptor potential (TRP) superfamily of non-selective cation channels. It has a systemic distribution with relatively high expression in kidney tubules. PC2 shares a common transmembrane fold with other TRP channels, in addition to having a extracellular/luminal domain (TOP domain) unique to TRPP and TRPML channels. Mutations in PC2 are associated with autosomal dominant polycystic kidney disease (ADPKD), which is one of the most prevalent genetic disorders in human. Despite that the genetic link between PC2 and ADPKD is well established, the molecular basis of the disease is still elusive. It has been proposed that dysfunction of ciliary PC2 is the main mechanism of pathology of PC2-associated ADPKD. Given the complex organisation of ciliary membrane, it is important to establish how PC2 interacts with specific lipids in its membrane environment. Lipid binding assay results suggest that detergent-solubilised PC2 can bind a range of phosphatidylinositol phosphates but not other simple anionic (phosphatidylserine, phosphatidic acid) or zwitterionic (phosphatidylethanolamine, phosphatidylcholine) lipids. Combining cryo-electron microscopy (cyro-EM) and multiscale molecular dynamics (MD) simulations, we identified a hydrophobic pocket in PC2 formed between S3, S4 transmembrane helices and S4-S5 linker, which showed a preference for phosphatidylinositol bisphosphate (PIP2) binding. Simulations of other members of the TRP channel family suggest this lipid-binding site may be shared amongst a number of TRP channels. In addition, our cryo-EM maps revealed a binding site for cholesterol on PC2, which is further characterised with MD simulations. These results help to position PC2 within an emerging model of the complex roles of lipids in the regulation and organisation of ciliary membranes. Moreover, we used MD simulations to probe the ion selectivity of PC2. Our results suggest that PC2 is selective for Na+ over Ca2+, and not only the selectivity filter residues but also the TOP domain contribute to the selectivity of the channel.